FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KESULITAN MENGINGAT DAN KONSENTRASI PADA USIA LANJUT DI INDONESIA TAHUN 2004 - Yuniati, Faiza (Publikasi Penelitian Terapan dan Kebijakan, 2008)
Elderly population increases from year to year in Indonesia, and has caused many social problems in elderly, physical diseases and also mental diseases. One of the mental diseases in elderly is Subjective complaints of memory and concentration. The goal of this research is to uncover the factors correlate with Subjective Complaints of Memory and Concentration in Indonesian elder people using a quantitative research with cross sectional design. Data resources in this research is a data of National Social Economic Survey integrated with Family Health Survey, year 2004.The result shown that prevalence of subjective complaints of memory and concentration is 12,5 %, known that factors correlate with subjective complaint of memory and concentration is age, disability in activity daily living, low self esteem and depression, disability in social activity, education, marital status, and behavior in consume fruits and vegetables.